Kaedah penyelesaian dalam menangani pertukaran agama di kalangan masyarakat Melayu- Islam di Johor, Selangor dan Wilayah Persekutuan Kuala Lumpur - Mohd. Yusof, Farahwahida; Timmiati, Sharifah Munirah; Nordin, Nur Raihan; Ruskam, Aminuddin; Suratman, Azmi Shah; Ripin, Mohd. Nasir (Centre for Islamic Studies and Social Development, 2008)
Cases on conversion of religion are regarded as sensitive by many quarters and have not been discussed openly. Indeed, statistics on conversion of religion are not exposed to the public. Recently the mufti of Perak, Datuk Dr. Harunsani Zakaria were reported to have been said that about 250,000 Muslims has converted to other religions. For example, the case of Noraisyah Bukhari has opened the eye of the Muslim society and created polemics and controversy. The issue was hotly and highly debated among Muslims in the country. The responses and reactions came not only among the layman Muslims but also from intellectuals and Muslims scholar and even the Malaysian government. For the meantime the debate on the issue seemed to be gaining momentum until various quarters including a few political parties which have urged the government to craft a legislation or enactment to address the issue of Muslims conversion to other of religion especially among the Malay-Muslims. Until now, the enactment is still in pre-discussion stage and will take a long time for approval and an implementation throughout the country. In the mean time, as waiting for the approval such laws to control the conversion religion among Malay-Muslims, rumors have started to circulate saying that the involvement of Malay-Muslims youngsters or adolescents are tempted to change their religion. They include those who are involved with groups which are visibly contradicted to Islam such as the Islamic Creed, Jangan Ikut Tuhan or JIT (Do not follow God) and Black Metal. Recently, a suggestion for an establishment of Interfaith Commission also created a concerns from the government because the suggestion would obviously create a rouse among Muslims in Malaysia. In relation to the issue, the government is called upon to give due attention and expose or publicize the statistics application of conversion religion identity among the Malay-Muslims to the Malaysian society because this phenomenon will effect and jeopardize the Muslim-family institutions in the country. This is therefore a serious matter at hand and more damaging than the social illness and drugs problems thus far. Even though there are many opinions, approaches and suggestions given before, still this matter has not been materialized yet. Therefore, a thorough study should be launched to look into the problem deeply. This study will help the government to identify the best solutions to overcome the conversion of religion issues among the Malay-Muslims in Johor, Selangor and Wilayah Persekutuan and the rest of the country.